Answers

2016-08-02T20:21:29+08:00
(x+7) (x+2)=0  all you have to do is find their factors and equate by zero.
x+7=0      x+2=0
    x= -7        x= -2
 The answer is -7 and -2
0
2016-08-02T21:53:05+08:00
I have answered this last nigth , 
ok here come;
 factoring:   (x+2) (x+7)=0;

x=-7  ; x=-2  ;
ilnitial plot;

------------o-----------o------I---
              -7             -2     0     open interval;

interval         (x+7)(x+2)               >0

x<-7               (-)    (-)  = + > 0      satisfy (inequality);
-7<x<-2          (+)  (-)   = - > 0      does not satisfy;
x>-2               (+)   (+) =+>0         satisfy;

hence : the solution set is {x/( x<-7, x>-2)} open interval;
here is your final graph;

/////////////////o-----------------o///////I/////////////;
     x         -7                    -2      0   x;

or solution set {x<-7 U x>-2} U stands for union
0